Pengaruh Kualitas Produk, Kualitas Pelayanan, Harga, dan Lokasi Terhadap Keputusan Pembelian Makanan di Warung Pojok Jeli Tulungagung - Ninditya Putri Hayuningtyas; Bayu Pramutoko; Nurali Agus N.Z (Institut Nalanda, 2023)
In the current era of globalization, business competition is becoming very tight, every business actor must always pay attention to the current conditions. Especially for culinary entrepreneurs, they must pay more attention to any influences that can influence purchasing decisions in businesses in the culinary field. It is very important to know the influence on purchasing decisions in every business. By knowing the effect of product quality, service quality, price and location on the decision to purchase food at Warung Pojok Jeli Tulungagung we can predict how the public will respond to the quality of the product that has been provided, the service that has been obtained, the price listed and the current business location so that they can make a plan. and fix it. The sampling technique in this study used the probability sampling method, while the samples taken were consumers who made purchases at Tulungagung Pojok Jeli Warung. The data was obtained by distributing questionnaires, observing and interviewing the owners, employees and consumers of the Tulungagung Pojok Jeli Stall. From the results of the study indicate that the variables of product quality, service quality, price and location have a significant effect on the buyer's decision. It is known from the results of the correlation analysis as follows: the value of r = 0.944 or 94.4%, which means that the magnitude of the correlation is close to 100%